1991
DOI: 10.1007/bf00588221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of EC-IC bypass surgery on resting cerebral blood flow and cerebrovascular reserve capacity studied with stable Xe-CT and acetazolamide test

Abstract: Cerebral blood flow (CBF) and cerebrovascular reserve capacity (CRC) were measured by stable xenon computerized tomography (Xe-CT) and acetazolamide test in 15 patients with cerebrovascular disease before and after extracranial-intracranial (EC-IC) bypass surgery for minor stroke, reversible ischemic neurological deficit or transient ischemic attack. All had angiographically shown occlusive lesions of the major arterial trunk. In the present series, global analysis showed that the bypass did not increase the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…After ECIC bypass, several studies have shown that there can be full or partial reversal of impaired CVR (Fig 6). 21,101,102 One study using 133 Xe SPECT in 28 patients who underwent ECIC bypass showed significant improvement of CVR after surgery while the resting CBF was essentially unchanged. 103 Schaller 104 concluded that the hemodynamic parameters observed in patients who experience improved neurologic function or diminished stroke risk profile after ECIC-bypass surgery contain both significantly elevated OEF and CBF/CBV.…”
Section: Pre-and Postoperative Evaluation Of Extracranialintracranialmentioning
confidence: 99%
“…After ECIC bypass, several studies have shown that there can be full or partial reversal of impaired CVR (Fig 6). 21,101,102 One study using 133 Xe SPECT in 28 patients who underwent ECIC bypass showed significant improvement of CVR after surgery while the resting CBF was essentially unchanged. 103 Schaller 104 concluded that the hemodynamic parameters observed in patients who experience improved neurologic function or diminished stroke risk profile after ECIC-bypass surgery contain both significantly elevated OEF and CBF/CBV.…”
Section: Pre-and Postoperative Evaluation Of Extracranialintracranialmentioning
confidence: 99%
“…The details of these specific procedures have been described elsewhere, 8,18,26 and their use for evaluating cerebral perfusion dynamics in moyamoya disease is well established. For Xe-CT, SPECT, and TCD studies, the summary findings for each report were utilized; in this way, numerical values for CBF and velocity were not recorded, but general findings such as, "normal," "impaired," and "exhausted" were.…”
mentioning
confidence: 99%
“…A MEDLINE (1985-2007) database search was conducted using the following keywords, singly and in combination: EC-IC bypass, hemodynamic failure, and misery 47 The authors of 15 of these studies used improved resting CBF and/or improved reactivity as an outcome. Of the 10 studies in which postsurgical resting CBF was reported, there was an increase in 5 studies 17,26,28,30,39 and an unchanged or decreased resting CBF in the other 5, 7,31,41,45 for a combined rate of 30% (34/113) of patients showing increased resting CBF.…”
Section: Literature Reviewmentioning
confidence: 99%